Implikasi Kerjasama Ekonomi Indonesia-China Bagi Indonesia: Studi Terhadap Project Kereta Cepat Jakarta-Bandung(KCJB) - Ahmad Aridho; Al Firman; Ruth Yessika Siahaan; Jojor Mindo; Armando Fidelis Wuwu; Prayetno Prayetno (International Forum of Researchers and Lecturers, 2023)
Indonesia's relations with China have been established diplomatically for more than 60 years, in some sources it is said that this relationship cannot be separated from Indonesia's foreign policy which is free and active in viewing international political constellations during the cold role, Foreign policy is a strategy or action plan designed by state decision makers to deal with other countries or any other international political entity, with the specific aim of achieving national interests defined in terms of national interests. Foreign actions taken by the government of a country aimed at fulfilling the national interests of a nation are carried out by the authorities at the time The cooperation between Indonesia and China in the construction of the Jakarta-Bandung high-speed train began with China's efforts to attract Indonesia's attention when President Jokowi attended the 22nd meeting of the Asia-Pacific Economic Cooperation (APEC) Summit in Beijing, China in November 2014.